2014
DOI: 10.1111/apha.12241
|View full text |Cite
|
Sign up to set email alerts
|

AltitudeOmics: exercise-induced supraspinal fatigue is attenuated in healthy humans after acclimatization to high altitude

Abstract: Aims We asked whether acclimatisation to chronic hypoxia (CH) attenuates the level of supraspinal fatigue that is observed after locomotor exercise in acute hypoxia (AH). Methods Seven recreationally-active participants performed identical bouts of constant-load cycling (131±39W, 10.1±1.4min) on three occasions: 1) in normoxia (N, PIO2, 147.1mmHg); 2) in AH (FIO2, 0.105; PIO2, 73.8mmHg); 3) after 14 days in CH (5,260m; PIO2, 75.7mmHg). Throughout trials, prefrontal-cortex tissue oxygenation and middle cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 54 publications
4
81
1
Order By: Relevance
“…Since vascular occlusion meant that changes in FIO 2 did not affect metabolic condition of the working muscles (as supported by the lack of difference in muscle tissue oxygenation between conditions), they attributed this impaired performance to a direct inhibitory effect of hypoxia on central motor drive, independent of muscle metabolic status. In support of this notion, Goodall et al (2014) found reduced cortical voluntary activation (i.e., index of supraspinal fatigue) and prefrontal tissue oxygenation (compared to baseline values) following constant-load cycling in acute hypoxia (FIO 2 : 0.105), while no reductions were observed in normoxia (Fig. 5).…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Since vascular occlusion meant that changes in FIO 2 did not affect metabolic condition of the working muscles (as supported by the lack of difference in muscle tissue oxygenation between conditions), they attributed this impaired performance to a direct inhibitory effect of hypoxia on central motor drive, independent of muscle metabolic status. In support of this notion, Goodall et al (2014) found reduced cortical voluntary activation (i.e., index of supraspinal fatigue) and prefrontal tissue oxygenation (compared to baseline values) following constant-load cycling in acute hypoxia (FIO 2 : 0.105), while no reductions were observed in normoxia (Fig. 5).…”
mentioning
confidence: 55%
“…*Different between pre-versus postexercise ( p < 0.05). FromGoodall et al (2014). Control (B) and CO 2 clamping () during incremental exercise in normoxia, hypoxia, and follow-up.…”
mentioning
confidence: 99%
“…Recent studies at severe altitude (5,260 m) documented that a chronic exposure to hypoxia (CH), which is associated with a substantial recovery of arterial O 2 saturation and content, can attenuate the development of central fatigue, but does not recover the exacerbated rate of development of peripheral fatigue observed during exercise in AH (19, 20). Based on the attenuated rate of central fatigue development in CH (vs. AH), which is mediated by the CNS benefiting from improved oxygenation (21), the aim of this review is to briefly discuss the impact of low O 2 availability on the functionality of CNS neuronal structures and to relate this relationship to hypoxia-related changes in whole body endurance capacity/performance.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to understand the impact of a prolonged stay at altitude on the development of central fatigue during exercise, Goodall et al (20) investigated corticospinal responses and central fatigue at SL (P I O 2 /S p O 2 = 147 mmHg/93%), in AH (74 mmHg/61%), and in CH (78 mmHg/78%; 14 d at 5,260 m above SL). Sea-level residents performed the identical bouts of locomotor cycling exercise (131 ± 39 W, 10 ± 1 min) in each of the three conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Supraspinal fatigue was assessed by pre-and post-exercise twitch response to femoral nerve stimulation and transcranial stimulation in 7 recreationally active subjects in normoxia, acute normobaric hypoxia (FIO 2 = 0.105) and after staying 14 days at 5260 m (Goodall et al, 2014). Improvement of the hypoxia-induced decline in post-exercise supraspinal fatigue with acclimatization to hypoxia was associated with an increased excitability of the brain to muscle pathway and with increased cerebral oxygen delivery as assessed by prefrontal near infrared spectroscopy and transcranial Doppler.…”
Section: Acclimatization To 5260 M Attenuates Exercise-induced Suprasmentioning
confidence: 99%